Electric Vehicle Fast Charging Integrated with Hybrid Renewable Sources for V2G and G2V Operation - Kumar S.; Khan K.R.; Srinivas V.L.; Shankar G.; Saket R.K.; Jana K.C. (My University, 2025)
In this article, the infrastructure required for the seamless and effective operation of Electric Vehicles (EVs) will be developing because electric vehicles are increasing exponentially on the road. One of them is vehicle-to-grid (V2G) technology. While a vehicle is parked or not in use, a V2G system transfers the battery's energy to the grid. In addition to helping the grid, V2G will also improve the efficiency of vehicles. The EV has been charged and discharged using a bi-directional DC-DC (BDDC) converter. The PI controller is used for BDDC and grid side inverter control. The electricity from the DC microgrid (DCMG) is utilized for EV battery charging in grid-to-vehicle (G2V) operation. DCMG has grid, solar PV, wind, and battery energy storage system (BESS) technologies. The fully loaded condition of the EV battery is taken into account. The modeling and verification of the strategy are performed in the MATLAB Simulink environment. © 2023 IEEE.